2011
DOI: 10.1111/j.1751-2409.2011.01030.x
|View full text |Cite
|
Sign up to set email alerts
|

Women and Men in Conflicting Social Roles: Implications from Social Psychological Research

Abstract: Despite legislation for gender equality in many nations, gender discrimination continues to be a problem. Psychological research from social role theory, the stereotype content model, and ambivalent sexism provide insights into the motivations behind gender inequality. This article reviews key research findings from these theoretical perspectives in the realm of gendered occupational inequalities and segregation. The emphasis of the article is on individuals fulfilling social roles that are perceived as confli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 75 publications
(184 reference statements)
5
26
0
1
Order By: Relevance
“…Moreover, hostile sexism (but not benevolent sexism) uniquely predicted tolerance for wife abuse among male and female undergraduates and community members in Turkey and Brazil . It is possible that these sexist ideologies may also underlie some of the barriers that men in nursing face as there are clear gender hierarchies in health care that men in nursing may be seen as violating (see Clow and Ricciardelli 2011).…”
Section: Perceptions Of Men In Nursingmentioning
confidence: 98%
See 3 more Smart Citations
“…Moreover, hostile sexism (but not benevolent sexism) uniquely predicted tolerance for wife abuse among male and female undergraduates and community members in Turkey and Brazil . It is possible that these sexist ideologies may also underlie some of the barriers that men in nursing face as there are clear gender hierarchies in health care that men in nursing may be seen as violating (see Clow and Ricciardelli 2011).…”
Section: Perceptions Of Men In Nursingmentioning
confidence: 98%
“…Although these theories were developed to address gender prejudice and discrimination targeting women, they appear equally applicable to the gender prejudice and discrimination experienced by men in female dominated professions (see Clow and Ricciardelli 2011), such as the issues reported by many male nurses internationally (the research cited in this paper comes from a wide variety of countries and samples; efforts have been made to indicate these details when a study is first mentioned). For example, male nurses in Taiwan have reported that they have to constantly reassure patients and visitors that they are "real" nurses (Yang et al 2004); men have faced historical systemic discrimination in nursing programs and hospitals in Canada, the United States, and the United Kingdom (Evans 2004); and male nursing students in Canada and the United States (and possibly elsewhere) face more stigma, ridicule, and barriers when pursuing nursing education than do their female counterparts (Bartfay and Bartfay 2007;O'Lynn 2004).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Dentre as explicações para este lento movimento, segundo alguns autores (CLOW & RICCIARDELLI, 2011;ENGEN, LEEDEN & WILLEMSEN, 2001;EAGLY & JOHNSON, 1990), está ainda a existência da discriminação e do preconceito quanto às características tidas como femininas. Segundo estes autores, a mulher é vista como sensível, solícita, compreensiva e simpática enquanto os homens têm como estereótipo ser mais decisivos, competentes, racionais, assertivos, agressivos, independentes, enérgicos, dominantes e autossuficientes.…”
Section: Introductionunclassified